Review on Immunomodulatory Nutraceuticals - Venkatachalam l, Dhanapal (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: A large number of plants and their isolated constituents have been shown to have potential immunity.In this review focusing on the immuno-modulatory activity of Ashwagandha (Withania somnifera) belonging to Solanaceae family and Neem (Azadirachta indica) belonging to Meliacea family. Methods: The Aswagandha churna was evaluated immunomodulatory activity byusing Albino wester rats and measured Delayed–type hypersensitivity response (DTH) (footpad swelling) and Percent neutrophil adhesion. The immuno-stimulatory effect of aswagandha root extract (WSE) evaluated by dexamethasoneinduced immunosuppressed mice in-vitro model. The immunomodulatory effectof Neem leaves infusion was evaluated by using broiler chicks, measuring theantibody titer determination against Infectious Bursal Disease (IBD) using ELISA Kit techniques.The effects of Neem on some hematological parameters were measured the Estimation of Packed Cell Volume (PCV) and total leucocyte count (TLC). Results: The results obtained from this study, Ashwagandha churna when orally administered the neutrophil adhesion (p<0.05) was significantly increased with the dose of 300mg kg -1day-1 when compared with untreated control indicating possible immune-stimulant effect, and the DTH response, which is a direct correlate of cell mediated immunity (CMI), was significantly increased at a doses of 200 and 300mg kg-1 day - In vitro immuno-stimulatory activity of Aswagandha root extract remarkably enhanced lymphocytes proliferation compared with the negative control (untreated cells). Both 2.5 μl and 5 μl of WSE (35 mg/ml) revealed significant (P < 0.001) stimulation of lymphocytes proliferation by approximately 322% and 403% respectively compared with the untreated cells. The immunomodulatory action of Neem leaves infusion; the mean antibody titer against IBD was higher for group C than all other groups. The effects of neem on some Hematological parameters of Packed cell volume of the control group was significantly lower than that of the treated groups at p<0.001, but with that of C2 at p<0.05. Conclusions: The current review on Immunomodulatory herbs shows great potential of herbs to cure or prevent certain diseases, which are beyond the reach of allopathic medicines in certain cases.